Vaccination to prevent human papillomavirus infections: From promise to practice. - Paul Bloem; Ikechukwu Ogbuanu (PLoS Medicine)
In an essay, Paul Bloem and Ikechukwu Ogbuanu discuss the public health implications of HPV vaccination.